Gambaran Derajat Keasaman (pH), Volume, Viskositas dan Kapasitas Buffer Saliva pada Anak Down Syndrome di Sekolah Luar Biasa Kabupaten Jember - Hamy Rafika Pratiwi; Sulistiyani Sulistiyani; Kiswaluyo Kiswaluyo (Pustaka Kesehatan, 2021)
Down syndrome is a congenital disorder that results in the inhibition of mental and physical development. People with down syndrome experience physiological changes in the flow rate of saliva and its composition. These changes will reduce the function of saliva in protecting teeth. The purpose of this study was to examine the salivary pH, volume, viscosity, and buffer capacity of children with down syndrome in Special Needs School Jember. This study was an observational study on 18 children from 3 Special Schools in Jember. The unstimulated saliva volume was determined by spitting methods, saliva viscosity using Ostwald viscosimeter, and salivary buffer capacity by Erricson methods. The results were the salivary pH was normal tends to be alkaline, the saliva volume was normal tends to low, the saliva viscosity was normal, and the buffer capacity of saliva was good. This will be useful to be taken into consideration for the dental and oral health program of down syndrome children